A simulation approach before using the industrial microcomputer controller - Zorman, Anton (Informatica (Ljubljana), 1988)
In this paper we describe a simulation packet that enables the verification of the software portion of the controller before implementating the controller on a real object. This program is unique of its kind, as far as we know, because it enables the examination of the controller's behavior in planner's workplace and so considerably reduces start expences. The simulation packet enables controlled execution of the user's program, clearly arranged writing out of data on the screen or on the printer and gives a chance for data modification.